ANTIMICROBIAL RESISTANCE PARTERN OF PATHOGENS CAUSING VENTILATOR ASSOCIATED PNEUMONIA IN NATIONAL HOSPITAL FOR TROPICAL DISEASES (Vietnam Journal of Community Medicine, 2026)
High burden of ventilator associated pneumonia (VAP) in Intensive Care Units results from multidrug resistance of pathogens.Objectives: To identify common pathogens as well as their antibiograms to building empiric therapy for VAP.Methods: A cross-sectional survey was carried out pathogens of VAP, diagnosed VAP according to CDC criteria, in Intensive Care Center at National Hospital for Tropical Diseases from 5/2023 – 4/2025.Results: There were 90 patients included with mean age of 68.7 ± 15,3 years, 83.0% was male, 60.0% having at least one comorbidity. Most common indications for invasive mechanical ventilation were pneumonia, sepsis and septic shock. Gram negative bacteria accounted for 99% VAP pathogens. Acinetobacter spp. was the most common pathogen accounted for 58.2%, Klebsiella spp. 19,4% and P. aeruginosa 14,6% with carbapenem resistance accounted for 100%, 85.0% and 80.0%, respectively. Especially, there was one strain of Klebsiella spp and one isolated P. aeruginosa showed resistant to colistin.Conclusions: The most prominent pathogens of VAP were Acinetobacter spp., Klebsiella spp. and P. aeruginosa with high ratio of carbapenem resistance and serious risk alarm with appearance of colistin resistance.
Keywords: Ventilator associated pneumonia, ventilator associated pneumonia pathogen, resistant to new beta-lactam, colistin resistance.